Wavelets : theory and applications - Louis, Alfred Karl, 1949- (Pure and applied mathematics (John Wiley & Sons : Unnumbered), 1997)
With applications in pattern recognition, data compression and numerical analysis, the wavelet transform is a key area of modern mathematics that brings new approaches to the analysis and synthesis of signals. This book presents the central issues and emphasizes comparison, assessment and how to combine method and application. It reviews different approaches to guide researchers to appropriate classes of techniques.